Identification of a potential DNA methyltransferase (DNMT) inhibitor - Zainab Jan (17306614) (2023)
DNA methyltransferases (DNMTs) play an important role in the epigenetic regulation of gene expression through the methylation of DNA. Since hypermethylation and consequent suppression of tumor suppressor genes are associated with cancer development and progression, DNA hypomethylating agents (HMAs) such as DNMT inhibitors have been proposed for cancer therapy. Two nucleoside analogues approved for the treatment of hematological cancers, decitabine and azacytidine, have poor pharmacokinetic properties, and hence there is a critical need for identifying novel HMAs. Virtual screening of a library of ∼40,000 compounds from the ZINC database, followed by molecular docking of 4,000 compounds having potential druggable properties with DNMT1, DNMT3A and DNMT3B were performed. One unique inhibitor (ZINC167686681) was identified that successfully passed through the Lipinski Rule of 5, geometry constraints as well as ADME/Tox filters and having strong binding energy for DNMTs. Further, molecular dynamics simulations of the docked complexes showed detailed structural features critical for its binding with the DNMTs and the stability of their interaction. Our study identified a compound with potential druggable properties and predicted to bind and inhibit DNMTs. Further investigations involving cellular and animal models of ZINC167686681 will help in potentially taking it into clinical trials for the treatment of cancers. Other Information Published in: Journal of Biomolecular Structure and Dynamics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/07391102.2023.2233637